Islamic Helix Quintuple Model in Ecosystem Strengthening Child-Friendly Schools in Madrasah - Siti Chadijah (Jurnal Manajemen Pendidikan, 2025)
Background This study examines the enabling factors behind successful Child-Friendly School (CFS) implementation in madrasah, a dimension often overshadowed in academic literature that predominantly documents barriers and failures. Purpose The purpose is to identify and analyze the enabling factors that support successful CFS implementation in madrasah. Design/method/approach Through a qualitative instrumental case study at MI An-Nizhamiyah Depok, data were gathered from in-depth interviews with 12 key informants, participatory observation, and document review, then analyzed using Miles, Huberman, and Saldaña's (2014) thematic framework with source, method, and theoretical triangulation. Results Two mutually reinforcing groups of enabling factors emerged: internal factors encompassing visionary school leadership, a rahmah-based organizational culture, an Islamic curriculum integrated with six CFS indicators, and a structured morning habituation program (Dhuha Prayer, Quranic recitation, tahsin-tahfidz) and external factors including Islamic foundation support, active parental participation, a Child-Friendly RT/RW ecosystem, the Depok Child-Friendly City (KLA) Nindya Category policy, and guidance from related government agencies. Contribution/value The central theoretical contribution of this study is the Islamic Quintuple Helix Model: an adaptation of Etzkowitz and Leydesdorff's (1995) Triple Helix that expands the actor base to five madrasahs, family, Islamic foundations, local Islamic community, and government bound together by Ukhuwah Islamiyah as the core social-spiritual capital. This model provides a contextual and replicable framework for other madrasah seeking to build resilient CFS ecosystems grounded in Islamic values.